PERBANDINGAN PRESTASI BELAJAR BAHASA JEPANG ANTARA MAHASISWA YANG MENJALANI PEMBELAJARAN LURING & PEMBELAJARAN DARING PADA PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Rahma Melia Sari; Merri Silvia Basri; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discusses the comparison of Japanese language learning achievement between students who undergo offline learning and online learning. The purpose of this study was to determine the comparison of Japanese language learning achievement. The method used in this research is quantitative with a descriptive approach. This study takes data from student achievement results in the 2019 odd semester and 2018 class in the 2020 odd semester. The results of this study indicate that of the 4 courses, 2 of them have the same learning achievement between offline learning and online learning. While the other 2 courses have significant differences between offline learning and online learning, where student learning achievement when learning online is better than when learning offline..Key Words: Comparison, Learning Achievements, Offline Learning, Online Learning,Japanese Laguange